6x+4=6x-3

Simple and best practice solution for 6x+4=6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+4=6x-3 equation:


Simplifying
6x + 4 = 6x + -3

Reorder the terms:
4 + 6x = 6x + -3

Reorder the terms:
4 + 6x = -3 + 6x

Add '-6x' to each side of the equation.
4 + 6x + -6x = -3 + 6x + -6x

Combine like terms: 6x + -6x = 0
4 + 0 = -3 + 6x + -6x
4 = -3 + 6x + -6x

Combine like terms: 6x + -6x = 0
4 = -3 + 0
4 = -3

Solving
4 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1.75x^3+2.5x^2=6.25x | | -17+x=63 | | (3x+5)-7=42 | | 4(1+4n)=-124 | | 3x+6=4x-17 | | 27x+9y=54 | | 4x-6-9x+1=0 | | 8(x-6)=-88 | | -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) | | 2(x+1)=3x-15 | | 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 | | 2x-4y+-6=0 | | 6y+15=9y |

Equations solver categories